First Medicolegal Forensic Entomology Case of Central Amazon: A Suicide by Hanging with Incomplete Suspension - Souza, Eduardo Rodrigues de; Rafael, José Albertino; Filho, Francisco Felipe Xavier; Da-Silva-Freitas, Juliana Oliveira; Oliveira-Costa, Janyra; Ururahy-Rodrigues, Alexandre (EntomoBrasilis, 2014)
This report describes the first medicolegal forensic entomology case of Central Amazon. A suicide by hanging took place in a “terra firme” primary forest on an upland plateau. The postmortem interval estimation was calculated on the basis of the biology of the blow fly Hemilucilia segmentaria (Fabricius) and also on the ecological succession pattern of the silphid beetle Oxelytrum cayennense (Sturm). This is the first case where the ecological information of a beetle was used as a forensic indicator in Brazil. Preliminary studies in the urban area of the city of Manaus, state of Amazonas, and in similar habitats of primary forest in the Reserva Florestal Adolpho Ducke, close to where the case occurred, were instrumental in helping the postmortem interval estimation. Primeiro Caso de Entomologia Médico-legal da Amazônia Central: Um Suicídio por Enforcamento com Suspensão Incompleta Resumo. Este relato descreve o primeiro caso de entomologia forense médico-legal na Amazônia Central. Um suicídio por enforcamento ocorrido em um platô de “terra firme” em floresta primária. A estimativa de intervalo pós-morte foi calculada com base na biologia da mosca varejeira Hemilucilia segmentaria (Fabricius) e também pelo padrão de sucessão ecológica do besouro silfídeo Oxelytrum cayennense (Sturm). Este é o primeiro caso onde as informações ecológicas de um besouro foram usadas como indicador forense no Brasil. Estudos preliminares realizados em área urbana na cidade de Manaus e em hábitat semelhante em floresta primária, na Reserva Florestal Adolpho Ducke, próximo do local onde o caso ocorreu, foram fundamentais para ajudar para a estimativa do intervalo pós-morte.